The influence of parent material (granite and schist) on physical and chemical properties of soils on the Syferkuil Experimental Farm - Maribeng, Lebea (University of Limpopo (Turfloop Campus), 2007)
The influence of parent material on physical and chemical properties of soil was studied on granite and schist derived soils on the Syferkuil Experimental Farm, situated in the Mankweng area of the Limpopo Province of South Africa. A total of 49 samples of virgin soils were collected, where granite soils constituted 26 samples and schist soils 23. The study design that was used is cross-sectional. The samples were analysed for physical and chemical properties. The physical properties of granite and schist soils were determined as percentages coarse sand, percentages medium sand, percentages fine sand, percentages very fine sand, percentages silt and percentages clay, whilst the chemical properties were determined as concentrations (cmol (+) kg-1) of Na, Mg, Ca, K ,ESP, CEC and P (mg kg-1), as well as pH. Statistical analysis of the results was performed by application of the Unpaired Student’s T Test, with the level of significance at p<0.05. The results showed that soils derived from granite had significantly higher coarse and medium sand fractions than schist soils; whereas schist soils were significantly higher in fine sand, very fine sand, silt and clay. The concentrations of Na, Ca, ESP and P, as well as CEC and pH in schist derived soils were higher than in granite derived soils although the differences were insignificant. However, significant differences occurred in K and Mg concentrations where schist derived soils had higher concentrations than granite derived soils. However, the concentrations of nutrient elements were found to be insufficient for proper production in agriculture. The sodium concentration was found to be low enough to not lead to sodic soil conditions. It was concluded that both granite and schist soils can be used for agriculture but require careful management because both soils indicated poor nutritional status.
Thesis (M.Sc. (Soil Science)) --University of Limpopo (Turfloop campus), 2007
Keywords: Granite soil; Schist soil; Soil properties; 551.0968; Soils -- South Africa -- Limpopo